Cavitation-erosion resistance of eutectic coatings in sodium chloride solution - Pashechko, M.; Holubets, V.; Zubrzycki, J.; Tisov, O. (Problems of Tribology, 2024)
The paper presents original research results related to the resistance of proprietary eutectic coatings applied to C45 structural steel to cavitation-erosion wear. This type of wear is encountered in devices operating in the chemical, petrochemical, heat and power industry and other industries. The research was conducted on a unique measuring stand developed by the authors. The research was conducted in a highly corrosive environment, i.e. sodium chloride solution. As a result of the research work, curves of the change in the electrode potential of C45 steel with different surface conditions and its polarization curves were obtained. Thanks to these curves, it was possible to determine the optimal method of protecting the tested steel against cavitation-erosion wear